Possibility of elimination of pathogen from Babesia infected animals by means of embryo transfer - Erdenetogtokh, P; Ganbat, S; Suzuki, Hiroshi (Mongolian Journal of Agricultural Sciences, 2014)
Babesia infections occur mainly in animals, and are transmitted by ticks. The severity of the diseases varies considerably depending on the species of Babesia involved as well as the immune response of the infected animal. In Mongolia infection produced by Babesia parasites is widely spread, provoking severe damage to the agricultural and economic sectors. Currently, strategies to control and prevent the infection are inefficient. Indeed, the necessity to look for suitable and accessible strategies to obtain animals free from the infection is needed. Currently, assisted reproductive technologies (ART) are used for the improvement of productivity in livestock. Moreover, embryo transfer seams to be useful approach to obtain clean embryos obtained from infected animals. Therefore, by using a mice model (ICR) infected with Babesia microti, an alternative method to obtain animals free from infection was examined. ICR mice at 8 weeks old were challenged with 0.2 ml of 1x107 IRBC/ml by i.p injection. After infection, superovulation was induced and then embryos were obtained and washed. Then, their development stage along with their morphological characteristics were monitored. In vitro embryos obtained from uninfected mice were used as a control group. The results indicate that the infection does not have any influence on pre-implantation embryonic development and morphological characteristics. Thus, we suggest that embryos obtained from infected animals might be useful for embryo transfer in order to improve productivity of livestock and reduce the risk of congenital infection. In summary, ART such as embryo transfer might be an useful technique in countries where Babesiosis is an endemic disease. DOI: http://dx.doi.org/10.5564/mjas.v11i2.214 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.36-42